Progressive Muscle Relaxation in the Elderly with Psychosocial Problems - Suhermi; Asnaniar, Wa Ode Sri (Pusat Kajian dan Pengelola Jurnal FKM UMI, 2020)
The impact of a person entering the elderly is a decrease in cognitive and psychomotor functions. Psychosocial changes in the elderly include changes in retirement, changes in personality aspects, changes in social roles in society, spiritual changes, changes in decreased sexual function and potential. With these disorders, the elderly need learning so that the elderly are able to prevent severe stressors by means of progressive relaxation. This activity aims to increase the knowledge of the elderly in the Malimongan Baru Health Center working area about progressive muscle relaxation exercises in an effort to deal with psychosocial problems. The method used was health counseling with lecture and discussion/question and answer strategies. Furthermore, providing training on progressive muscle relaxation movements. Training is conducted every Friday morning which takes 15 to 30 minutes. Evaluation was carried out with a pre-posttest to see changes in the level of depression of the elderly using the Yesavage Geriatric Depression Scale questionnaire. The results showed that there was a decrease in the level of depression experienced by the elderly. A total of 25 elderly people who experienced mild depression and 5 elderly people who experienced moderate depression. It is hoped that the Puskesmas will conduct mental health counseling in every health examination. So that the elderly are not only physically healthy but can also be mentally healthy and progressive muscle relaxation exercises become an exercise option for the elderly.